The American Constitution and the Treaty Making Power - John J. Parker (Washington University Law Quarterly, 1954)
The exercise of the treaty making power, the power of dealing with foreign nations, presents a subject of peculiar difficulty to a federal state such as ours in which the component states exercise sovereign power in local matters, for treaty making does not relate, as some persons seem to think, only to matters lying beyond the boundaries of the country. Treaties regulate our relationships with foreign nations and peoples; and these relationships concern matters which are subject to regulation at our end of the relationship by the several states of our union. Treaties of friendship, commerce and navigation relate to the rights of our citizens to trade, travel and carry on business in foreign countries and of the citizens of such countries to carry on like activities here. Some of the matters dealt with, such as foreign commerce and the navigation of rivers and other navigable waters, are matters which, in the absence of treaty, would be subject to the control of the federal government. Others, such as the right to own and inherit property, to carry on business in corporate form, to practice professions, etc., are matters which, in the absence of treaty, would be subject to the powers of the several states. Treaties must deal with all of these matters; but it is perfectly clear that it would never do to have the several states entering into treaties with foreign nations with regard thereto. The treaty making power must be centered in the national government which represents all of the states and must be exercised by it not only with respect to matters which, in the absence of treaty, would be subject to the control of the federal government, but also with respect to those, which in the absence of treaty would be within the control of the states. In no other way could a federal state deal satisfactorily with foreign nations; and the failure of the Confederation, which existed prior to the adoption of the Constitution, to provide some such centralized power for handling foreign affairs was one of the chief sources of its weakness and failure.
Keywords: Treaties; Constitutional law -- United States